Optimization of execution time for second-floor house extension using the critical path method (cpm) - Nurhasanah, Andi; Revalina, Rizsyawal; Usnaini, Usnaini; Rifai, Muhammad; Prapdopo, Prapdopo (Enrichment : Journal of Management, 2025)
A This study discusses the application of the Critical Path Method (CPM) to optimize the execution time of a two-story house extension project. Through network analysis, CPM helps identify the critical path and determine which activities must be prioritized to ensure the project is completed on time. The analysis results show that the project duration can be shortened to 41 days by effectively managing critical activities and utilizing float time optimally. Therefore, CPM has proven to be an effective tool in improving the scheduling efficiency of construction projects